2019
DOI: 10.1002/hep4.1401
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Screening in an Underserved U.S. Cohort of Reproductive Age Women

Abstract: The opioid epidemic has recently increased the rates of hepatitis C virus (HCV) infection among young women. We therefore aimed to characterize the cascade of HCV care in a cohort of underserved women of reproductive age. Medical records of 19,121 women between the ages of 15 and 44 years, receiving primary care in the San Francisco safety‐net health care system, were reviewed. Cohort characteristics were as follows: median age 33 years (interquartile range 26‐38), 18% white (12% black, 46% Latina, 22% Asian, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…1-4 While the number of treated patients has increased, the number of untreated, infected patients continues to be significant. [5][6][7][8][9][10][11][12][13] A study of predominantly African American (AA) patients in our university medical practice, during the interferon era (2002)(2003) and prior to the introduction of DAAs (2012-2013), confirmed that the AA population was within the age cohort for our patients through 2013. 5 While this aging cohort has traditionally represented the bulk of patients with HCV, the possibility that younger patients will be identified in recent populations is an important area of investigation.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…1-4 While the number of treated patients has increased, the number of untreated, infected patients continues to be significant. [5][6][7][8][9][10][11][12][13] A study of predominantly African American (AA) patients in our university medical practice, during the interferon era (2002)(2003) and prior to the introduction of DAAs (2012-2013), confirmed that the AA population was within the age cohort for our patients through 2013. 5 While this aging cohort has traditionally represented the bulk of patients with HCV, the possibility that younger patients will be identified in recent populations is an important area of investigation.…”
Section: Introductionsupporting
confidence: 58%
“…The opioid epidemic appears to be an important contributor for the increase in younger populations being infected with HCV. 7 This has been associated with HCV infections and may be contributing to an increasing challenge for the eventual eradication of HCV. Support of this observation is found in multiple reports of an increase in HCV in younger individuals between 2006 and 2019, although many of these studies had significantly fewer AA as compared to non-AA patients.…”
Section: Introductionmentioning
confidence: 99%
“…( 16 , 17 ) Linking new mothers to care could improve not only their own health through seeking cure but also follow‐up for their HCV‐exposed infant and prevent vertical transmission in future pregnancies. Few studies describe HCV referral and treatment practices in women diagnosed with HCV during pregnancy, ( 5 , 17 , 18 , 19 , 20 , 21 ) and only one describes HCV treatment in the DAA era, with improved treatment rates for a limited number of postpartum women compared to the general population. ( 20 )…”
mentioning
confidence: 99%
“…Few studies describe HCV referral and treatment practices in women diagnosed with HCV during pregnancy, ( 5 , 17 , 18 , 19 , 20 , 21 ) and only one describes HCV treatment in the DAA era, with improved treatment rates for a limited number of postpartum women compared to the general population. ( 20 )…”
mentioning
confidence: 99%
“…12 These medication advances suggest that the primary barriers to HCV elimination are preventing new transmissions, diagnosing those who are infected, and improving access to and completion of curative therapy, all of which are factors that can be influenced by psychosocial and structural factors. 13,14 With respect to these barriers, HCV testing is still below recommended rates in certain healthcare settings, 15 which is especially notable as the US Preventive Services Task Force expanded its screening recommendation to include all adults. 16 Prior studies examining the HCV cascade of care identified younger age, mental illness, and active substance use as risk factors for being lost to follow-up after a diagnosis is made.…”
mentioning
confidence: 99%